Klasifikasi Kemurnian Daging Sapi Berbasis Electronic Nose dengan Metode Principal Component Analysis - Fachri Rosyad; Danang Lenono (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
Meat is a widely consumed food, therefore it requires certain quality standards to be safe to consumed and does not harm the consumers. Several of those standards including meat freshness and meat purity. Recently it has been found some cases of pork adulteration in beef which consequently could harm the consumers. In order to examine the purity of beef, it required test method based on odor characteristics by using electronic nose.Adulterated beef samples were prepared with pork content within samples varied by 20%, 40%, 60%, and 80% of total sample mass where the sample mass is 20 grams. The 10 days data collecting consists of sensing and flushing cycles for 180 seconds each cycles, with 6 times process repeating over 1 day. Data processing was carried out in several stages which including signal preprocessing based on baseline manipulation, feature extraction by calculating the area of the response signal curve by using trapezoidal rule of integral approximation, and multivariate analysis using PCA.Cumulative percentage of variance of two principal components of beef and pork classification test yields at 99.9% of total variance, and classification test between pure beef and adulterated beef resulting in 99.6% of total variance. Therefore, it can be concluded that electronic nose can classify between pure beef and adulterated beef.